The chemical composition and events related to the cytotoxic effects of propolis on osteosarcoma cells: A comparative assessment of Colombian samples - Mora, Dolly Patricia Pardo; Santiago, Karina Basso [UNESP]; Conti, Bruno José [UNESP]; de Oliveira Cardoso, Eliza [UNESP]; Conte, Fernanda Lopes [UNESP]; Oliveira, Lucas Pires Garcia [UNESP]; de Assis Golim, Marjorie [UNESP]; Uribe, Jaime Fabian Cruz; Gutiérrez, Rafael María; Buitrago, Mauricio Rey; Popova, Milena; Trusheva, Boryana; et al. (Wiley, 2019)
Osteosarcoma (OSA) is a type of bone cancer showing an aggressive biological behavior with metastatic progression. Because propolis potential for the development of new antitumoral drugs has been indicated, we evaluated the chemical composition of Colombian propolis samples and the mechanisms involved in their cytotoxic effects on OSA cells. The chemical composition was analyzed by GC–MS and the DPPH free radical scavenging activity was measured. Cluster and principal components analysis were used to establish an association with their inhibitory concentration 50% (IC 50 ). Cell viability was analyzed by MTT assay; apoptosis was determined by flow cytometry; mitochondrial membrane permeability and reactive oxygen species were evaluated by rhodamine 123 and DCFH-DA. Transwell assay was used to evaluate the invasiveness of propolis-treated cells. Samples were grouped: Cluster 1 contained diterpenes and benzophenones and showed the highest antiradical activity; Cluster 2 was characterized by triterpenes, fatty acid, and diterpenes. Usm contained diterpenes and triterpenes different of the other samples and Sil contained triterpenes and flavonoids. Apoptosis, mitochondrial membrane alteration, and suppression of cell invasion were the main mechanisms involved in the inhibition of OSA cells in vitro, suggesting the potential of Colombian propolis to discover new antitumor drugs.
Keywords: apoptosis; chemical composition; cytotoxicity; mitochondrial membrane potential; osteosarcoma; propolis